Educational orchestral how the object of scientific cognition is (Pedagogy of Higher and Secondary Education, 2007)
The important questions of methodological bases of functioning of training pops orchestra are considered. In the article Theauthor approached the problem of teaching and education of students in the pops orchestra guiding by strong scientific knowledge’s.
Keywords: performance; conductor; composer; bandsman; technical possibilities and performing interpretation of the work; interpretation; dynamic nuances; agogica